Identification and characterization of Dof genes in Cerasus humilis - Liu, Weili; Ren, Weichao; Liu, Xiubo; He, Lianqing; Qin, Chen; Wang, Panpan; Kong, Lingyang; Li, Yang; Liu, Yunwei; Ma, Wei (Frontiers in Plant Science, 2023)
Dof genes encode plant-specific transcription factors, which regulate various biological processes such as growth, development, and secondary metabolite accumulation. We conducted whole-genome analysis of Chinese dwarf cherry (Cerasus humilis) to identify ChDof genes and characterize the structure, motif composition, cis-acting elements, chromosomal distribution, and collinearity of these genes as well as the physical and chemical properties, amino acid sequences, and phylogenetic evolution of the encoded proteins. The results revealed the presence of 25 ChDof genes in C. humilis genome. All 25 ChDof genes could be divided into eight groups, and the members of the same group had similar motif arrangement and intron-exon structure. Promoter analysis showed that cis-acting elements responsive to abscisic acid, low temperature stress, and light were dominant. Transcriptome data revealed that most ChDof genes exhibited tissue-specific expression. Then, we performed by qRT-PCR to analyze the expression patterns of all 25 ChDof genes in fruit during storage. The results indicated that these genes exhibited different expression patterns, suggesting that they played an important role in fruit storage. The results of this study provide a basis for further investigation of the biological function of Dof genes in C. humilis fruit.